The Wonder and Spirit of Phenomenology and Theology: Rubenstein and Derrida on Heidegger's Formal Distinction of Philosophy from Theology - Capretto, Peter (Heythrop journal, 2014)
While Heidegger's earlier phenomenological writings inform much contemporary discourse in the continental philosophy of religion, his 1927 essay on ‘Phenomenology and Theology’ offers a largely uncontested distinction between philosophy and theology on the basis of their possibilities as sciences following ontological difference. This paper reconsiders Heidegger's distinction by invoking spirit and wonder, concepts Jacques Derrida and Mary-Jane Rubenstein have more recently emphasized as central to thought that is open to that which ruptures metaphysical schemas. I contend Heidegger's use of ontological difference as a formal distinction between philosophy and theology distances us from the wonder, spirit, and truth (alētheia) that undoes the binaries behind which we take shelter. However, I temper this critique with the recognition that Heidegger, Derrida, and Rubenstein equally recognize an inescapable repetition of metaphysical thinking in the philosophy of religion.